Educator Parenting Competence as a Mediator Between Human Resource Management and Students Courtesy Development - Marvianasari, Reni; Noorhidayati, Salamah; Teguh (Al-Qalam Institue, 2025)
This research was motivated by the fact that some students still behave impolitely when speaking to their peers. Some speak loudly, while others use profanity or social media slang (e.g., “anjay,” “you ask”). This study employs a concurrent mixed-method approach, combining quantitative and qualitative data through questionnaires, observations, interviews, and documentation. The population consisted of 2,663 students, with a sample of 95 determined using the Yamane/Slovin formula. Quantitative data were analyzed using SPSS, while qualitative data underwent condensation, presentation, and conclusion drawing/verification. Results show that teachers’ Human Resources (HR) and parenting quality significantly influence children’s manners. Teachers’ HR mostly met good criteria (68%), parenting quality was mostly very good (70%), and children’s manners were mostly very good (60%). There is a significant influence between teachers’ HR and children’s manners, as well as between parenting quality and manners. Managerial implications suggest that educational institutions should integrate HR management strategies—such as targeted training, performance evaluation, and supportive work environments—to strengthen teachers’ interpersonal and pedagogical skills. This alignment between HR policies and classroom practices can foster a culture of courtesy, thereby shaping students into individuals with strong moral character.